Positive news culture: Flood framing in China - NING, LI; Ting, Su Hie (Social Sciences & Humanities Open, 2025)
Flood is an environmental hazard causing soil erosion, leading to not only damage of vegetation but also to water contamination and spread of diseases. In China, the positive reporting culture shapes flood coverage by emphasising government responses and crisis management, reinforcing public trust and social stability. The study examined the flood framing by a national newspaper (People’s Daily) and a regional newspaper (Zhengzhou Daily) published in China. A total of 194 news articles on flood published between January 1 and December 31, 2023 were analysed. People’s Daily attributed more salience to flood news (179 articles) than Zhengzhou Daily (15 articles). The analysis showed that both newspapers predominantly utilised episodic framing (People’s Daily, 99.4 %; Zhengzhou Daily, 100 %). Through the positive valence of articles (70.9 %), People’s Daily set the agenda for the readers to showcase President Xi Jinping’s direct involvement in flood mitigation and highlight his compassion to victims. In contrast, Zhengzhou Daily had only 26.7 % of articles with positive valence. The larger percentage of articles with negative valence (53.3 %) alerts readers to the destruction and challenges caused by floods. The responsibility frame dominated in both newspapers. The second frequent frame dimension in People’s Daily is economic consequences of flood and whereas Zhengzhou Daily uses human interest elements to engage with readers. People’s Daily as the official voice box of the central government exudes propaganda even in crisis reporting.